Rare aetiology of abdominal pain: contained abscess secondary to perforated jejunal diverticulitis - Yeung, Enoch (BMJ Case Rep, 2020)
A patient with a history of multiple jejunal diverticulosis (JD) presented with a non-peritonitic abdominal pain and leucocytosis. CT scan showed a thick-walled interloop collection within the left mid-abdomen with dilated bowels and mild diffuse air-fluid levels. Exploratory laparotomy revealed multiple diverticular outpouchings in the mid-jejunum, one of which was perforated, contained within the mesentery. Resection of the contained abscess and primary anastomosis were performed subsequently.